Program for Improving Facilities and Tourist Attractions at the Culture and Tourism Office of North Sumatra Province - Furqan, Furqan; Hutauruk, Indah Swanti; Putra, Yogi (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
Tourist attractions are places for tourists to visit. In this research, object facilities and tourist attractions are important things for a tourist attraction to increase tourist visits in North Sumatra. So far, tourism management by the North Sumatra regional government has been under the authority of the Culture and Tourism Department. This department is the party responsible for planning, development and regulations and providing guidance to the tourism industry in the region as a whole. The formulation of the problem in this research is (1) What is the program for developing tourist facilities and tourist attractions in North Sumatra? (2) What are the facilities development programs in the field of object development and tourism businesses? (3) What efforts have been made to improve tourist facilities and attractions in North Sumatra? The method used by researchers in this research is a descriptive research method using a qualitative approach.